Critical evaluation of portable Raman spectrometers: From rock outcrops and planetary analogs to cultural heritage - A review - Jehlička, Jan; Culka, Adam (Analytica chimica acta, 2022)
This review focuses on the progress made and recent developments regarding the use of portable Raman spectrometric devices in the geosciences as well as with scientific testing of objects of cultural heritage. By utilizing different types of Raman spectrometric devices - from the modular; through systems operating with optical heads mounted via optical fibers; to the compact, lightweight, and handheld - are herein described and critically evaluated. The wide range of applications under indoor and closed environments (museums, collections, religious buildings, etc.) are reviewed, and the more commonly used for characterization of art in the broadest sense, as well as fully outdoor investigations (e.g., on rocky outcrops; of the minerals, microbiological colonization, etc.), and including extreme Earth environments and projects with exo-planetary research potential. The rapid acquisition of relevant spectroscopic data and the non-destructiveness of the analyses and diagnostics are greatly appreciated by art historians and conservators on the one hand, as well as by mineralogists, geoscientists, microbiologists on the other. The various environments investigated and the broad range of compounds that can be detected by obtaining their Raman spectra have demonstrated the vast potential of portable, and especially handheld, Raman spectrometer devices for on-site applications.
Keywords: Minerals; Spectrum Analysis, Raman; Ramanova spektroskopie; Mineralogy; Cultural heritage; minerály; Geoscience; Portable Raman spectrometers; Biomarkers